2021
DOI: 10.1111/1440-1681.13493
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of roflumilast under cerebral ischaemia/reperfusion injury in juvenile rats through NLRP‐mediated inflammatory response inhibition

Abstract: This study aims to investigate the protective effect of roflumilast, a phosphodiesterase (PDE)‐4 enzyme inhibitor, and demonstrate its possible role in the development prevention of cerebral ischemia/reperfusion injury (CI/RI) after stroke induced by carotid artery ligation in juvenile rats. The rats were randomly divided into five groups: healthy group without any treatment, healthy group administered with 1 mg/kg roflumilast, CI group not administered with roflumilast, CI group administered with 0.5 mg/kg ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(66 reference statements)
2
2
0
1
Order By: Relevance
“…Endovascular treatment of AIS enables routine pathological examination of cerebral arterial thrombosis. e current studies found that the pathological features of the acute cerebral arterial occlusive thrombus were similar to postmortem pathological examinations [17]. Whether from the heart or arteries, the thrombi have similar structural features and cannot simply be classified as a red or white thrombus.…”
Section: Discussionsupporting
confidence: 66%
“…Endovascular treatment of AIS enables routine pathological examination of cerebral arterial thrombosis. e current studies found that the pathological features of the acute cerebral arterial occlusive thrombus were similar to postmortem pathological examinations [17]. Whether from the heart or arteries, the thrombi have similar structural features and cannot simply be classified as a red or white thrombus.…”
Section: Discussionsupporting
confidence: 66%
“…Several groups have demonstrated in vitro neuroprotective activity of roflumilast [29]. Roflumilast has been shown to decrease IL-1β, IL-6, and TNF-α and the number of apoptotic neurons in the brain after subarachnoid hemorrhage (SAH) [9]. Our results are in line with the previous studies that have demonstrated that roflumilast prevents EAE-induced increase in pro-inflammatory induced cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Roflumilast was dissolved in Saline: DMSO (98:2, v/v). FTY720 was used as positive control and dissolved in saline [9,39]. Treatment doses of roflumilast and FTY720 were selected according to the previous studies.…”
Section: Chemicals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…AST seviyeleri incelendiğinde LPS grubundaki AST seviyesinin sağlıklı gruba göre anlamlı şekilde arttığı görülmüştür (p<0,05). Akut veya kronik organ hasarları karaciğerin de dahil olduğu kalp, akciğer, böbrek, pankreas, beyin, gonadlar ve bağırsaklar gibi birçok organda görülebilir [45,[47][48][49]. Karaciğer enfeksiyöz olan veya olmayan birçok ajanla hasara uğrayabilir [50,51].…”
Section: Ast Ve Alt Sonuçları (Ast and Alt Results)unclassified